Revision of the Costa Rican species of Elachiptera (Diptera: Chloropidae) - Mlynarek, Julia J.; Wheeler, Terry A. (Zootaxa, 2008)
The Costa Rican species of the genus Elachiptera are revised. There are seven described species in the region: Elachiptera attenuata (Adams); E. coniotrigona Duda; E. fucosa sp. n. (type locality: Costa Rica: Santo Domingo de Heredia); E. melinifrons sp. n. (type locality: Costa Rica: San José); E. queposana sp. n. (type locality: Costa Rica: Quepos); E. rubida Becker and E. sacculicornis (Enderlein). An additional species (Elachiptera sp. A) is known from a single female specimen and is not formally described. Only one of these species (E. attenuata) had previously been recorded from Costa Rica.